Applying the Multiple Streams Framework in Westminster systems: A comparative case study of pay-for-performance policymaking in primary health care in England and New Zealand - Verna Smith (International Review of Public Policy)
The Multiple Streams Framework has been criticised for failing to recognise the strong institutional drivers of policymaking in Westminster-type jurisdictions, thereby limiting its relevance for explaining policymaking in such jurisdictions. There has been much recent scholarship exploring its relevance for such jurisdictions. However, a new method has been developed to analyse the application of this popular Framework to case studies of policymaking episodes, using a set of hypotheses to test the Framework’s predictive power. This provides an opportunity to further address two key questions: the applicability of the Multiple Streams Framework to Westminster systems, and the more general question of the relationship between institutions and the Multiple Streams Framework. The research reported here has applied the new method to two episodes of health policymaking in two centralised Westminster jurisdictions with closely aligned political, policymaking and health systems, England and New Zealand. The process and outcomes of each policymaking episode, and the relevance of the Multiple Streams Framework for explaining them using the new method, are presented. While the hypotheses are found to be valid for the policymaking process and outcomes in the English policymaking episode, this is not the case for the New Zealand episode. The findings show that there is a need for greater recognition of the strong influence of institutional factors in the Multiple Streams Framework, particularly in the decision-making stages of the policy processes, especially with regard to policymaking in centralised Westminster jurisdictions.